1996
DOI: 10.1177/44.1.8543780
|View full text |Cite
|
Sign up to set email alerts
|

CD66a (BGP), an adhesion molecule of the carcinoembryonic antigen family, is expressed in epithelium, endothelium, and myeloid cells in a wide range of normal human tissues.

Abstract: CD66a, also called biliary glycoprotein (BGP), is a member of the carcinoembryonic antigen (CEA) family and of the immunoglobulin superfamily. CD66a is the human homologue of Cell-CAM, a well-defined cell adhesion molecule of the rat. In the present study a monoclonal antibody specific for CD66a was used to locate CD66a in human tissues. CD66a is expressed in epithelia, in certain endothelia, and in cells of the myeloid lineage. Hepatocytes were stained along the bile canaliculi. A characteristic apical membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
130
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(139 citation statements)
references
References 3 publications
6
130
3
Order By: Relevance
“…In contrast to the putative tumor suppressive functions, CEACAM1 is not expressed in several normal epithelial tissues (Prall et al, 1996), including thyroid as shown by our current studies. It has also been found to be upregulated in primary lung carcinomas when compared with adjacent normal lung tissue (Ohwada et al, 1994;Wang et al, 2000).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In contrast to the putative tumor suppressive functions, CEACAM1 is not expressed in several normal epithelial tissues (Prall et al, 1996), including thyroid as shown by our current studies. It has also been found to be upregulated in primary lung carcinomas when compared with adjacent normal lung tissue (Ohwada et al, 1994;Wang et al, 2000).…”
Section: Discussioncontrasting
confidence: 66%
“…CEACAM1 is an example of a transmembrane protein widely expressed by epithelial and endothelial cells, and most types of hematopoietic cells tissues (Prall et al, 1996;Obrink, 1997;Singer et al, 2000;Plunkett and Ellis, 2002). CEACAM1 shows both homophilic adhesion Ocklind, 1984 1446/id as well as heterophilic binding to other CEA family members in vitro (Oikawa et al, 1992) and is believed to be an important player in maintenance of normal tissue architecture.…”
Section: Introductionmentioning
confidence: 99%
“…However, when considered more closely, it is noteworthy that all the isolates from men bound CEACAM5 whereas only two-thirds of the isolates from women did so. Interestingly, in this regard, squamous cells of the lower genital tract tend to express CEACAM5 whereas columnar epithelial cells of the female endocervical and upper genital tract instead express CEACAM1 (27). While CEACAM family expression within the male urethra has not been mapped, the difference in receptor specificities of the recovered isolates makes it enticing to consider whether there is selection for CEACAM5 binding at this site.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial CEACAMs (CEACAM1, CEACAM5, and CEACAM6) are all presumed to facilitate bacterial colonization (25,26). In the female genital tract, squamous epithelia express CEACAM5, whereas CEACAM1 is expressed on columnar epithelia of the endocervix and uterus (27), allowing each to be accessible for direct docking by the gonococci. Moreover, CEACAM1 is widely expressed on lymphocytes, and CEACAM1-induced signaling can influence immune cell activation (28)(29)(30)(31)(32)(33)(34)(35), potentially providing a mechanism for immune evasion by N. gonorrhoeae.…”
mentioning
confidence: 99%
“…12 The present study was designed to investigate the expression pattern of CEACAM1 in the human placental components and thus its potential implication in implantation and placentation. To investigate the expression of CEACAM1, immunohistochemistry on paraffin-embedded specimens and flow cytometry on isolated trophoblast was performed using the mAb 4D1/C2, 13,14 which had been previously used to study expression in several normal human tissues, 15 as well as expression in normal and malignant mammary gland and in endometrial neoplasia. 16,17 …”
mentioning
confidence: 99%